CONTRIBUTION OF ADVERTISING AND SALES PROMOTION IN SHAPING CONSUMER PURCHASING DECISIONS AT RUBY SUPERMARKET CAKRANEGARA - Anggriani, Rini; Cahyadi, Irwan; Jati, L Jatmiko (Distribusi - Journal of Management and Business, 2025)
In this study, the main problem raised in this study is whether advertising and sales promotion have a significant influence either simultaneously or partially on consumer purchasing decisions at Ruby Supermarket Cakranegara? In accordance with these problems, the purpose of this study is to determine the significance of the influence of advertising and sales promotion on consumer purchasing decisions at Ruby Supermarket Cakranegara both simultaneously and partially. The type of research used is quantitative research and uses a sample survey method in collecting data. The data collection tool used is a questionnaire, with the analysis tool used in accordance with the researcher's objectives is Multiple Linear Regression Analysis, which is then continued with the F test and t test at alpha 5%. In accordance with the objectives of the study, it was found that advertising and sales promotion variables have a significant influence on consumer purchasing decisions at Ruby Supermarket Cakranegara both simultaneously and partially. The significance criteria are known based on the F test and t test that have been carried out, where F count and t count have higher values ​​than F table and t table. Based on the results of the t test. The suggestion that can be given according to the research results is that in order to increase sales, the policy that should be the main orientation of Ruby Supermarket Cakranegara is to improve the quality of advertisements that are less attractive to potential consumers so that they are more interested in making purchases.